2017
DOI: 10.1007/s00453-017-0277-5
|View full text |Cite
|
Sign up to set email alerts
|

New Bounds for the CLIQUE-GAP Problem Using Graph Decomposition Theory

Abstract: Halldórsson et al (ICALP proceedings of the 39th international colloquium conference on automata, languages, and programming, vol part I, Springer, pp 449-460, 2012) investigated the space complexity of the following problem CLIQUE-GAP(r, s):In particular, they give matching upper and lower bounds for CLIQUE-GAP(r, s) for any r and s = c log(n), for some constant c. The space complexity of the CLIQUE-GAP problem for smaller values of s is left as an open question. In this paper, we answer this open question. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…We can 3-approximate MIS for a stream of unit squares in the plane using Õ(α(G)) space, and achieving better than a 5 2 -approximation to α(G) requires Ω(n) space. Unit interval intersection graphs given as an explicit vertex stream require Ω(n) space to get a better than 5 3 approximation to α(G), making it harder than the implicit stream equivalent. Figures 2 and 1 illustrate these results and put them in context to previously known bounds (see also Section 1.3).…”
Section: Our Contributionsmentioning
confidence: 99%
See 3 more Smart Citations
“…We can 3-approximate MIS for a stream of unit squares in the plane using Õ(α(G)) space, and achieving better than a 5 2 -approximation to α(G) requires Ω(n) space. Unit interval intersection graphs given as an explicit vertex stream require Ω(n) space to get a better than 5 3 approximation to α(G), making it harder than the implicit stream equivalent. Figures 2 and 1 illustrate these results and put them in context to previously known bounds (see also Section 1.3).…”
Section: Our Contributionsmentioning
confidence: 99%
“…A corresponding Õ n 2 c 2 space random sampling algorithm shows this is tight up to logarithmic factors. Braverman et al [5] showed that space Ω( m c 2 ) is needed, even if c = o(log n), where m is the number of edges of the input graph. This bound though only holds for small values of m.…”
Section: Prior Workmentioning
confidence: 99%
See 2 more Smart Citations
“…These well-known limitations of sampling motivated an alternative class of techniques based on sketching or streaming algorithms. Here, custom online algorithms and data structures are designed for specific metrics of interest that can yield provable resource-accuracy tradeoffs (e.g., [17,18,20,31,36,38,43]).…”
Section: Introductionmentioning
confidence: 99%